Evaluación de la ansiedad en madres con hijos en condición de discapacidad (2016)
In order to assess the levels of anxiety in mothers with children in disability status, is an investigation of non-experimental quantitative type - descriptive cross-sectional. Where obtained as a result levels of severe anxiety with physiological, cognitive and motor symptoms associated with this.